Integrative Learning in US Undergraduate Public Health Education: A Review of Student Perceptions of Effective High-Impact Educational Practices at Georgia State University - Armstrong-Mensah, Elizabeth; Ramsey-White, Kim; Alema-Mensah, Ernest (Frontiers in Public Health, 2019)
In 2003, the United States (US) Institute of Medicine of the National Academies recommended that all undergraduate students have access to an education in public health to assist with diversifying the public health workforce and ensuring an educated citizenry on public health issues. In line with this recommendation, and that of the Consensus Conference on Undergraduate Public Health Education, Georgia State University established a Bachelor of Science in Public Health (BSPH) program in 2016, with the mission of advancing health through leadership, scholarship, research, and service, to better the human condition and to promote the common good, especially for urban communities in the US and for global populations. Using integrative approaches that encourage student empowerment, self-development, integrative thinking, and reflective learning, the Georgia State University BSPH program currently offers a range of generalist introductory public health courses to over 400 students. This review seeks to examine student perceptions of integrative practices utilized by Georgia State University faculty in the BSPH program and to investigate the extent to which student perceive these integrative educational practices as preparing them to use insights gained in the classroom and from the field, to question, modify, connect, and integrate material learned in the academic setting, to real-life public health challenges. It also seeks to identify which of the integrative educational practices have the highest impact of helping students integrate the knowledge and skills gained to public health issues.